History, Status, and Future of Oyster Culture in France - Buestel, Dominique; Ropert, Michel; Prou, Jean; Goulletquer, Philippe (Journal of Shellfish Research, 2009)
The history of French oyster culture consists of a succession of developmental phases using different species, followed by collapses caused by diseases. The indigenous species Ostrea edulis was replaced first with Crassostrea angulata, then C. gigas. France is now the top producer and consumer of oysters in Europe, producing around 120,000 t of the cupped oyster C. gigas annually, and an additional 1500 t of the flat oyster O. edulis. Cupped oysters are produced all along the French coast from natural and hatchery spat. Various structures are used to collect spat from the wild. After a growing-on period, oysters are Cultivated by three main methods: (1) on-bottom culture in the intertidal zone or in deep water, (2) off-bottom culture in plastic mesh bags in the intertidal zone, or (3) suspended Culture on ropes in the open sea. The main recent development is the increasing use of hatchery oyster spat, especially triploids. Almost all oyster production is sold fresh and eaten raw straight from the shell. There is marked seasonality in sales, with the majority being made during Christmas and New Year. Abundant production and the lack of market organization induce strong competition among the production areas, causing prices to fall. Oyster farmers have developed strategies of sales promotion and regional quality labeling to overcome this difficulty. There are numerous production hazards, including environmental crises (microbiological pollution), unexplained mortality, and overstocking, and recent problems with toxic algae have disrupted oyster sales. However, oyster Culture has many assets, including a coastal environment offering favorable sites for Mollusc growth and reproduction. Oysters have been consumed in France since ancient times, and their culture is now well established with a concession system that favors small family firms. There is a young, well-educated farmer population, with technical expertise and savoir faire. Careful seawater quality monitoring ensures good consumer protection, and research is ...